A time-dependent offset field approach to simulating realistic interactions between beating hearts and surgical devices in virtual interventional radiology - Wang, Haoyu; Wu, Jianhuang (Frontiers in Cardiovascular Medicine, 2022)
Endovascular interventional radiology (IR) is a minimally invasive procedure for the treatment of vascular diseases. This procedure requires physicians to be highly skilled at manipulating interventional devices under the guidance of 2-dimensional X-ray imaging. By offering a non-error-sensitive and radiation-free environment, a virtual reality-based simulator provides a promising alternative for surgical skills training and surgery planning. Building a realistic and interactive simulator is a challenging task. To achieve better realism, this paper proposes a novel method of simulating the heartbeat for both standard and patient-specific anatomical data. A time-dependent offset field approach is proposed to efficiently and stably simulate the interactive behavior between the dynamic heart mesh and surgical devices. For medical imaging simulation, we propose a GPU-based linear depth subtraction method to approximate fluoroscopic images based on the attenuation of the X-ray. On this basis, a topology-based flow map method is proposed to simulate the propagation of the contrast medium in angiography. The experimental results show that the beating heart mesh can interact with surgical devices stably in real-time. Under the simulated fluoroscopic imaging effect, the injected contrast medium can realistically visualize both dynamic and static vessels. Moreover, a preliminary evaluation made by medical students and clinicians demonstrates that our simulator is effective in surgical skills training and surgery planning.